Synthesis of Cyclic Hexapeptides via the Hydrazide Method and Evaluation of Their Antibacterial Activities - Yunfei Cui; Meng Liu; Binghui Ruan; Zhouyuji Liao; Xue Tang; Dongting Zhangsun; Yong Wu; Sulan Luo (Molecules)
Antimicrobial peptides (AMPs) have emerged as promising candidates in the fight against multidrug-resistant pathogens due to their broad-spectrum antimicrobial activity and low potential for resistance development. However, their clinical application is limited by poor stability and susceptibility to enzymatic degradation. This study aims to address these limitations by synthesizing a series of cyclic hexapeptides using the hydrazide method and evaluating their antimicrobial activity and stability. The hydrazide method facilitated the synthesis of 11 cyclic peptides through a reaction between C-terminal hydrazides and cysteine-containing peptides. Antimicrobial assays showed that Cy-f2 and Cy-f4 exhibited potent inhibitory effects against different kinds of bacteria, including E. coli, Staphylococcus aureus, and S. aureus. Hemolysis assays revealed minimal red blood cell lysis at effective antimicrobial concentrations, indicating good biocompatibility. Stability tests demonstrated improved stability of the cyclic peptides compared to linear counterparts in SGF and 80 °C. In conclusion, the cyclic hexapeptides synthesized in this study demonstrate excellent antimicrobial activity, enhanced stability, and low toxicity, suggesting their potential as new candidates for treating drug-resistant bacterial infections.